KNOWLEDGE, WORKLOAD, ATTITUDE, AND ELECTRONIC HEALTH RECORDS COMPLIANCE AMONG HEALTHCARE PROFESSIONALS - Ibrahim, Rita Zahara; Supriyantoro, Supriyantoro; Joyo, Ericko Ongko (UI Scholars Hub, 2023)
Electronic health record (EHR) has replaced conventional medical records in Indonesia. Until now, its utilization is still not optimal, and there are still frequent problems with incomplete filling of the EHR form due to individual factors. To examine the association between knowledge and workload with healthcare professionals' (HCPs) compliance in filling out HER, considering the mediating role of attitude. We performed a cross-sectional study on 80 HCPs who worked at the Intensive Care Unit of the National Cardiovascular Centre Harapan Kita. We observe the level of knowledge and workload as independent variables, attitudes as mediating variables, and compliance as the dependent variable. Primary data were obtained by using questionnaires. The association among observed variables was analyzed using path analysis. As a result, we found that knowledge, workload, and attitude simultaneously had a significant association with compliance in EHR filling. Attitude is the most dominant independent variable that directly affected compliance, while knowledge and workload were associated with compliance mediated by attitude. It was concluded that increasing HCPs' compliance in filling out the EHR would be directly associated with a positive attitude of HCPs. A higher level of knowledge and a lighter workload do not directly associate with better compliance, but affect attitude improvement. Thus improving knowledge levels and adjusting the workload will increase EHR filling compliance by mediating positive attitudes among HCPs.